2006
DOI: 10.1021/ac061029+
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Two-Dimensional Capillary Electrophoresis Analysis of Barrett's Esophagus Tissues

Abstract: We have constructed a high-speed, two-dimensional capillary electrophoresis system with a compact and high-sensitivity fluorescence detector. This instrument is used for the rapid and reproducible separations of Barrett's esophagus tissue homogenates. Proteins and biogenic amines are labeled with the fluorogenic reagent 3-(2-furoyl)quinoline-2-carboxaldehyde. Labeled biomolecules are separated sequentially in two capillaries. The first capillary employs capillary sieving electrophoresis using a replaceable sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 41 publications
1
77
0
Order By: Relevance
“…Capillary electrophoresis was performed on a locally constructed instrument employing postcolumn laser-induced fluorescence detection with a sheath-flow cuvette [10,[13][14]. Excitation was provided by a 473 nM laser (Lasermate Group, Pomona, CA, USA).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary electrophoresis was performed on a locally constructed instrument employing postcolumn laser-induced fluorescence detection with a sheath-flow cuvette [10,[13][14]. Excitation was provided by a 473 nM laser (Lasermate Group, Pomona, CA, USA).…”
Section: Instrumentationmentioning
confidence: 99%
“…These products can have dramatically different electrophoretic behavior, leading to an envelope of peaks producing complex electropherograms [4][5][6]. Most of our work has been with FQ, which converts cationic lysine residues into neutral products, which can be detected with exquisite sensitivity [7][8][9][10]. More importantly, we have shown that the incorporation of an anionic surfactant, such as SDS, results in the collapse of the multiple labeling envelope into a single, sharp peak [7].…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution 2-D separation was achieved in 1990 by coupling HPLC with CE [35]. Two-dimensional CE with different separation modes has also been demonstrated for proteomics application [36]. Such a 2-D separation scheme employs two columns or capillaries.…”
Section: Two-dimensional Protein Separation In Two Intersected Channelsmentioning
confidence: 99%
“…As one of the most sensitive techniques, fluorescence detection is widely used in protein research [7][8][9][10][11]. Although native fluorescence emitted by aromatic amino acid residues (such as ଝ This paper is part of the special issue "Enhancement of Analysis by Analytical Derivatization", Jack Rosenfeld (Guest Editor).…”
Section: Introductionmentioning
confidence: 99%